Constraints Perceived in Adoption of Groundnut Production Technology - Kumar, Manoj; Sharma, F.L.; Kalash, Poonam (Indian Journal of Extension Education, 2012)
Groundnut is the principal oilseed crop of India and plays an important role in economy of the nation. Rajasthan is one of  the major groundnut producing states of the country. The agro-climatic zone IVa (Sub-humid Southern Plain and Aravali  Hills) is major groundnut producing zone of the state but productivity of this crop is very low in this agro-climatic zone.  This has been basically due to non-adoption of improved package of practices of groundnut cultivation by majority of the  farmers. The present study was conducted in this zone to find out the major constraints which prevented the farmers from  adoption of groundnut production technology. It was found from the study that 45.83, 40.84 and 13.33 per cent farmers  were in the low, medium and high constraints level respectively. It was further observed that inadequate skill for seed  treatment, unavailability of technical advice for crop cultivation, poor knowledge of high yielding varieties,  unavailability of improved tools in the local market, inadequate irrigation facilities, unavailability of credit at marginal  interest rate, high cost of plant protection chemicals, high cost of seed of HYVs, scarcity of moisture in the soil, delay in  occurrence of monsoon, were important constraints perceived by the groundnut growers in adoption of groundnut  production technology. It was also found that there was a significant variation among large, small and marginal groundnut  growers with respect to constraints perceived by them in adoption of groundnut production technology.
Keywords: Groundnut; Agro-climatic zone; constraints; Adoption